2013
DOI: 10.1177/0022487113488144
|View full text |Cite
|
Sign up to set email alerts
|

The Current State of Assessment Education

Abstract: In response to the existing accountability movement in the United States, a plethora of educational policies and standards have emerged at various levels to promote teacher assessment competency, with a focus on preservice assessment education. However, despite these policies and standards, research has shown that beginning teachers continue to maintain low competency levels in assessment. Limited assessment education that is potentially misaligned to assessment standards and classroom practices has been ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(48 citation statements)
references
References 31 publications
0
43
0
5
Order By: Relevance
“…Teachers are struggling with data systems, time use and lack of knowledge about how to use data to improve instruction (Anderson et al, 2010;Goertz, Olah, & Riggin, 2010;Valli & Buese, 2007;Wayman et al, 2012). Overall, research has shown that teachers are insufficiently prepared to effectively integrate assessment results into their practice (DeLuca & Bellara, 2013;Wayman, & Jimerson, 2014). It is, however, striking that existing research has not sufficiently investigated how teachers use test data to help pupils to improve their learning results.…”
Section: National Test Data and Teachers' Workmentioning
confidence: 99%
“…Teachers are struggling with data systems, time use and lack of knowledge about how to use data to improve instruction (Anderson et al, 2010;Goertz, Olah, & Riggin, 2010;Valli & Buese, 2007;Wayman et al, 2012). Overall, research has shown that teachers are insufficiently prepared to effectively integrate assessment results into their practice (DeLuca & Bellara, 2013;Wayman, & Jimerson, 2014). It is, however, striking that existing research has not sufficiently investigated how teachers use test data to help pupils to improve their learning results.…”
Section: National Test Data and Teachers' Workmentioning
confidence: 99%
“…Research indicates that many experienced and able classroom practitioners serving as supervising teachers lack confidence themselves in deploying data in their teaching-both in terms of analysing and learning lessons from prior assessment data and using data to draw conclusions about students' learning progress (DeLuca & Bellara, 2013;Reeves, 2017). Hence, it is again understandable that it is hard to find any substantial discussion about PSTs engagement with standard 5.4 (Demonstrate the capacity to interpret student assessment data to evaluate student learning).…”
Section: Discussionmentioning
confidence: 99%
“…The value and importance of valid, reliable assessment data to inform decision-making and to plan monitoring is uncontested (William et al, 2004;DeLuca and Bellara, 2013;Epstein et al, 2015;Wise and Smith, 2016). Brown (2017), however, highlights the inconvenient truth that our assumption that assessment data are always trustworthy and subject to appropriate scrutiny is a fallacy.…”
Section: Assessment To Support Learningmentioning
confidence: 99%